Enhanced solar energy harvest in dye-sensitized solar cells using silver-doped TiO2 Photoelectrodes via Spray Pyrolysis - Piranave Sritharan; Meena Senthilnanthanan; Punniamoorthy Ravirajan; Dhayalan Velauthapillai; Gamaralalage Rajanya Asoka Kumara; Balraju Palanisamy (Chemical Physics Impact, 2025)
This study focuses on doping TiO2 with trace amounts of Ag⁺ ions, employing spray pyrolysis to prepare the Ag-doped TiO2 photoelectrode for application in Dye-Sensitized Solar Cells (DSSCs). In this regard, Ag-doped TiO2 nanomaterials were initially synthesized from Titanium(IV) isopropoxide (TTIP) with varying concentrations of Silver nitrate (AgNO3). The structural and optical characterizations of the synthesized nanomaterials confirmed the presence of TiO2 in pure anatase phase and enhanced light absorption, respectively. The morphological characterization of Ag-doped TiO2 nanomaterials revealed spherical shaped particles. Subsequently, the DSSCs were fabricated using Ruthenium-based N719 dye and imidazolium iodide/ triiodide redox couple as the sensitizer and electrolyte, respectively. Photovoltaic performances were evaluated under simulated solar irradiation (100 mW cm−2, 1 sun, AM 1.5). The optimized device with 3 mmol % Ag-doped TiO2 photoelectrode exhibited PCE (η) of 8.32 %, which was about 13 % greater than the device with un-doped TiO2 (η = 7.35 %). The observed upsurge in PCE is due to the 10 % increase in short-circuit current density (JSC) value resulting from enhancement in visible light absorption which was confirmed by UV–Visible spectroscopic analysis. Moreover, an improved electron transport in the Ag-doped TiO2 based device was confirmed by electrochemical impedance spectroscopic study which is ascribed to the significant reduction in charge recombination. These findings demonstrate the potential of Ag-doped TiO2 for enhanced DSSC performance, offering a viable pathway for improving solar energy conversion efficiency.